1992
DOI: 10.1007/bf00235262
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of mixed function oxidase systems in polychlorinated biphenyl metabolism by plant cells

Abstract: Nineteen different polychlorinated biphenyl (PCB) congeners ranging in chlorine content from 2 to 6 chlorine atoms were provided to nonphotosynthetic suspension cultures of rose (Rosa sp. cv. Paul's Scarlet). After a 96 h incubation period, 11 individual congeners had been metabolized by > 10%. Provision of mixed function oxidase inhibitors (10 mM metyrapone or 0.5 mM 7,8-benzoflavone) either stopped or severely reduced the metabolism of individual congeners; whereas (inhibitors of peroxidase) (1 mM benzoate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…The second and third types were set up by addition of 1 mL of 1 mM n-propylgallate or 1 mL of 1 mM 1-aminobenzotriazole solution as enzyme inhibitors. n-propylgallate is known to be a plant peroxidase inhibitor and 1-aminobenzotriazole is a plant P-450 inhibitor (Lee & Fletcher 1992;Mackova et al 2001). The controls were subjected to the same procedures as the experimental replicates.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…The second and third types were set up by addition of 1 mL of 1 mM n-propylgallate or 1 mL of 1 mM 1-aminobenzotriazole solution as enzyme inhibitors. n-propylgallate is known to be a plant peroxidase inhibitor and 1-aminobenzotriazole is a plant P-450 inhibitor (Lee & Fletcher 1992;Mackova et al 2001). The controls were subjected to the same procedures as the experimental replicates.…”
Section: Methodsmentioning
confidence: 98%
“…any differences among 2,2¢-PCB, 2,4¢-PCB and 4,4¢-PCB) cannot be determined. Previous reports have pointed out that the position of the chloride substitutes does affect the metabolic rates of PCBs (Lee & Fletcher 1992). In Lee & Fletcher's (1992) study, almost all the congeners subject to metabolism had a single substitution in the 2-position of the molecule, and it was concluded that variations in the conformation of different PCBs may explain their metabolism within plant cells.…”
Section: Degradation Of Pcbsmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, they are produced from microbial metabolism of dibenzofuran, fluorene, and carbazole (26). Furthermore, many reports have now shown that plants metabolize major environmental contaminants such as PCBs to generate hydroxylated derivatives (9,10,21,22,23,28).…”
mentioning
confidence: 99%
“…Selective application of these agents, such as inhibitors and inducers of cytochrome P450, monooxygenases, and peroxidases (Canivenc et al, 1989;Chroma et al, 2002;Cole and Owen, 1987c;Lee and Fletcher, 1992), aids the identification of metabolic relationships and the sites of oxidative enzyme attack, and can be used to modify degradation pathways. This advantage is shared by hydroponic systems, as chemical effectors can also be added readily to hydroponic media.…”
Section: Metabolic Studiesmentioning
confidence: 99%